Aluminum stress and lime application affect growth, yield, and disease resistance of wheat (Triticum aestivum L.) varieties under acidic soil conditions - Gebreyes Gurmu; Sheleme Beyene; Yihenew G. Selassie (Agrosystems, Geosciences & Environment, 2025)
Abstract Aluminum toxicity in acidic soils reduces wheat productivity by inhibiting root growth, disrupting nutrient uptake, and causing physiological stress. This study aimed to investigate the effect of Al stress on wheat varieties under limed and unlimed acidic soils. Fourteen bread wheat varieties were screened for acid tolerance under lath‐house conditions using acidic soil. From the screening activity, Balcha (tolerant variety) and Dursa (sensitive variety) were chosen and evaluated with five rates of Al application (0, 25, 50, 75, and 100 mg kg−1 soil) under limed and unlimed soil conditions. The experiment was conducted in lath‐house laid down in factorial arrangement using a completely randomized design with six replications. The results showed that increased Al levels significantly reduced root and shoot length and biomass in both wheat varieties, with maximum reductions at the highest Al rate. Under unlimed conditions, Dursa exhibited greater susceptibility to Al toxicity, with root length and biomass reductions of 82.3% and 69.3%, respectively, compared to Balcha, which displayed stronger tolerance. Soil acidity tolerance indices confirmed Balcha's resilience, with relative root length outperforming Dursa by 337%. Al‐induced stress increased leaf blotch severity, with Dursa showing higher infection (46.1%) than Balcha (34.4%). However, lime application significantly reduced severity, particularly in Dursa by 89.5%. Grain yield decreased by 23% at the highest Al rate. Lime application effectively mitigated Al toxicity, improving growth, yield, and disease resistance. Combining lime application with acid‐tolerant varieties such as Balcha presents a viable strategy for managing soil acidity and improving wheat production.